Millennial-scale climate variability recorded in Late Pleistocene coastal deposits of Formentera Island (Balearic Archipelago, Western Mediterranean). (20th April 2022) - del Valle, Laura; Timar-Gabor, Alida; Pomar, Francesc; Pons, Guillem X.; Fornós, Joan J.
Abstract: Pleistocene aeolian deposits interbedded with marine deposits, colluvial deposits and palaeosols are observed in area of Es Copinar, Caló d'es Mort and Es Ram-s'Estufadors in Formentera Island. The sedimentary succession outcropping along the south-eastern coast of the island is characterized by a well-exposed high-resolution succession representing the main climate and geomorphological changes that occurred in this part of the western Mediterranean during the late Pleistocene. In this study we present the sedimentology and stratigraphy of carbonate sandstone, marine deposits, breccias and the aeolian-alluvial interaction deposits and silty facies, which allow describing ten major sedimentary units. Optically stimulated luminescence (OSL) dating and the biochronostratigraphic fauna from the marine deposits indicate that their deposition took place during the Last interglacial-glacial cycle, and their succession recorded Heinrich and Dansgaard-Oeschger events (DO). In this sense, dryer and cold Heinrich events led to the formation of extensive coastal dune fields when the sea level dropped. On the other hand, relatively warmer and wetter DO events drove the development of palaeosols and the aeolian-alluvial interaction deposits.